EFFECTS OF IMPLEMENTATION OF WATER-SAVING IRRIGATION TECHNOLOGIES IN COTTON GROWING ON SOIL SALINITY REGIME - А. K. Juraev; O. M. Yusupova (Web of Journals Publishing, 2025)
This article discusses the impact of water-saving technologies on soil salinity during the cultivation of the "Bukhara-8" variety in the conditions of the Bukhara region. During the experiments, it can be seen that the amount of salts in the soil is relatively low and a favorable environment is created for the growth of the plant in the case of watering cotton by laying a black polyethylene film on the soil.
Keywords: Bukhara-8 variety of cotton, hydrogel granule, black polyethylene film, amount of salts, chlorine ion, dry residue. Soil moisture before watering.